A critical discourse analysis of the toxic free nutritious meal in The Jakarta Post: Teun A. van Dijk’s framework - Semartini, Atur (Privietlab, 2026)
Free Nutritious Meals (MBG) is a flagship program promoted by President Prabowo Subianto and Vice President Gibran Rakabuming Raka during the 2024 General Election campaign. In its implementation, the program has faced numerous challenges, one of which is the high number of food poisoning cases among students after consuming the MBG menu. The media reported on the poisoning case, including The Jakarta Post. News stories do not reflect reality but construct it. This study investigates the discourse of toxic Free Nutritious Meals constructed by The Jakarta Post using Teun A. van Dijk’s Critical Discourse Analysis approach. The data consisted of four online news articles obtained from thejakartapost.com, published at four different times. The news texts were analyzed through textual, social, and social cognition analyses, as proposed by Van Dijk. The findings reveal that The Jakarta Post constructs food poisoning cases as incidents that require serious attention from both the public and the government. However, at the same time, the newspaper also builds a discourse portraying the government as having responded to the cases promptly and the MBG program as generally well implemented.